Sharon Thompson, Quiet Revolutionaries: The Married Women's Association and Family Law (Bloomsbury Publishing, 2022) - Porter, Antonia (feminists@law, 2023)
Review of Sharon Thompson, Quiet Revolutionaries: The Married Women's Association and Family Law (Bloomsbury Publishing, 2022).